1993
DOI: 10.2355/isijinternational.33.915
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Comminution Techniques for the Surface Modification of Powder Materials.

Abstract: This paper reviews a new method for surface modification to cover particle surface with fine particles mechanically in a dry phase by making use of comminution techniques.First, the relation of comminution process with surface modification technology is discussed, and the advancedmachinesdeveloped in Japan to treat core particles surface with fine particles based on grinding principles are introduced. Then, the details of the composite process of core/fine particles with these machines are explained.In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 0 publications
0
60
0
1
Order By: Relevance
“…Naito et al reported that composite particle fabrication using a Mechanofusion system results in a decrease in the specific surface area of processed particles, compared with that of unprocessed particles. 21) In this study, after application of intermittent shear stress to lactose particles using a ThetaComposer ® , the specific surface area of surface-processed lactose decreased. The mechanism of this decrease may be as follows.…”
Section: Results and Discussion Physical Properties Of Lactose Carriementioning
confidence: 99%
“…Naito et al reported that composite particle fabrication using a Mechanofusion system results in a decrease in the specific surface area of processed particles, compared with that of unprocessed particles. 21) In this study, after application of intermittent shear stress to lactose particles using a ThetaComposer ® , the specific surface area of surface-processed lactose decreased. The mechanism of this decrease may be as follows.…”
Section: Results and Discussion Physical Properties Of Lactose Carriementioning
confidence: 99%
“…By using this mechanical treatment process, we can obtain nanocomposite particles; in this process, nanoparticles are bonded to submicron particles by applying an external mechanical force, especially shear force. 10) For example, we have reported the direct bonding of TiO2 particles to Si3N4 particle by mechanical treatment, and it is possible to fabricate nanoparticle-dispersed Si3N4 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on the fabrication of advanced ceramics by using a powder composite process in which nanopar ticles are mechanically mixed using only a dry mixing process, which allows us to obtain nanocomposite particles. In this process, nanoparticles are bonded to submicron particles by applying an external mechanical force, specifically a shear force 1,2) . Many types of powder composite processes have been developed commercially 1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…In this process, nanoparticles are bonded to submicron particles by applying an external mechanical force, specifically a shear force 1,2) . Many types of powder composite processes have been developed commercially 1,2) . These nanocomposite particle processes are divided into two types: the bonding of fine particles to a core particle and the homogeneous mixing of various fine particles.…”
Section: Introductionmentioning
confidence: 99%